Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.
KerkoCite.ItemAlsoKnownAs: 2405685:WVVB6PCG

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Districts of Teaching Excellence Sierra Leone - Beoku-Betts, Iman; Burgess, Flic (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14794031 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1090 ZenodoArchiveConcept: 14794030
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Strengthening the use of data for decisions on teacher deployment in Sierra Leone: A Geospatial Approach to Workforce Allocation - McBurnie, Chris; Frazer, Madleen Madina; Dube, Gugulethu; Godwin, Katie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14608646 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1082 ZenodoArchiveConcept: 14608645
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Data-Driven Teacher Deployment in Sierra Leone: Practicalities and quantitative analysis of using a matching algorithm in the 2024/25 deployment cycle - Koutecký, Tomáš; Mackintosh, Alasdair; Huti, M; Adam, Taskeen; Godwin, Katie; Frazer, Madleen Madina (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368231 ZenodoArchiveConcept: 15368230 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1115 2405685:ICRSXHTV 2405685:MUWUTSZS 2486141:MRAYINR3
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Teacher Deployment in Sierra Leone Using a Geographic Information System-Supported Preference Matching Algorithm: A systems analysis - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368298 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1116 ZenodoArchiveConcept: 15368297
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15039164 ZenodoArchiveConcept: 15039163 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1103 2405685:IRFH43RX 2405685:SFNCI64Z 2486141:C9Q4ZDTR
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Transforming Teacher Deployment: Lessons from a matching algorithm tool - Frazer, Madleen Madina; Adam, Taskeen; Godwin, Katie; Mackintosh, Alisdair; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368169 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1114 ZenodoArchiveConcept: 15368168
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14749795 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1089 ZenodoArchiveConcept: 14749794
Keywords: _r:AddedByMyEducationEvidence

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence